Engineered feldspar-based ceramics: A review of their potential in ceramic industry. Issue 2 (February 2022) - Fuertes, V.; Reinosa, J.J.; Fernández, J.F.; Enríquez, E.
Abstract: Feldspars are the most abundant mineral in the earth's crust, however, their interest in ceramic industry goes beyond their abundancy. The unique compositional and structural features as well as the many outstanding properties that feldspars own, make them to be widely used as raw material for the ceramic industry. Moreover, multiple works have demonstrated that engineered feldspar-based ceramics are very promising for their use in applications such as ceramic tiles, dielectrics or phosphors, among others, and therefore, in this article, a comprehensive review on their dielectric, mechanical, optical and thermal properties is presented. This review intends to provide an up-to-date outlook of the possibilities that engineered feldspars offer to their application in ceramic industry, discussing future prospects and challenges that might ease the opening up of new horizons for future applications in ceramic sector.